EFFECTS OF SELF-MASSAGE WITH FOAM ROLLER ON FLEXIBILITY AND OTHER MOTOR SKILLS – LATEST RESEARCH REVIEW - Pavlović, Aleksandra; Denić, Lazar; Knežević, Olivera (Sport - nauka i praksa, 2023)
During the past decade, self-massage of the muscular fascia using a foam roller (FR) has become an increasingly common way of supplementing traditional methods of soft tissue treatment, while both professional and recreational athletes use it as a tool for warm-up and/or post-training relaxation. Considering the relevance of this topic among researchers, coaches, and physiotherapists, the aim of this this paper is to present a narrative review with the systematization of the latest research on the effects of foam rolling on motor skills. Publication search was conducted using the following databases: Google Scholar, PubMed, and ScienceDirect. The following keywords were used in the search: foam rolling, self-myofascial release, fascia, and muscle soreness. The selection of papers was based on the following criteria: 1) publications written in English and published in the period 2019-2022, and 2) original scientific papers focused on examining the effects of soft tissue massage using FR on the range of motion (ROM), motor abilities (strength, power, speed, balance and others), acute muscle pain, and delayed muscle soreness. Recent research results confirm earlier findings that FR can have short-term, positive effects on flexibility and ROM, while findings regarding the effects on muscle strength, explosive power, and balance are equivocal. In addition, it has been noted that this type of treatment can delay the onset of fatigue, and alleviate the painful sensitivity of muscles after intensive work-out. Although foam rollers have been in use for a long time both in sports and in rehabilitation, due to the heterogeneity of methods applied in related studies, there is still no official recommendation on the optimal way of applying these tools (treatment duration, pressure and cadence, i.e. the frequency of vibration if such a roller is used).